2019
DOI: 10.1001/jamapediatrics.2018.5199
|View full text |Cite
|
Sign up to set email alerts
|

Association of Infant Temperament With Subsequent Obesity in Young Children of Mothers With Gestational Diabetes Mellitus

Abstract: Infant temperament is associated with excess weight gain or childhood obesity risk in samples of healthy individuals, although the evidence has been inconsistent. To our knowledge, no prior research has examined this topic among children exposed to gestational diabetes mellitus (GDM) in utero. OBJECTIVE To prospectively evaluate infant temperament in association with overweight and obesity status at ages 2 to 5 years among children born to mothers who experienced GDM. DESIGN, SETTING, AND PARTICIPANTS This pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 43 publications
(72 reference statements)
1
11
0
Order By: Relevance
“…This was evident for participants in control clinics, wherein a significant association between greater infant negative affectivity and more frequent use of food to soothe was noted. These findings are consistent with previous research illustrating greater infant negative affectivity predicts more frequent use of food to soothe, 5,6,48 greater feeding frequency, 49,50 and earlier introduction to complementary foods and beverages, most often via addition of cereal to the bottle, 51,52 likely because feeding effectively reduces fussing and crying 19 …”
Section: Discussionsupporting
confidence: 90%
“…This was evident for participants in control clinics, wherein a significant association between greater infant negative affectivity and more frequent use of food to soothe was noted. These findings are consistent with previous research illustrating greater infant negative affectivity predicts more frequent use of food to soothe, 5,6,48 greater feeding frequency, 49,50 and earlier introduction to complementary foods and beverages, most often via addition of cereal to the bottle, 51,52 likely because feeding effectively reduces fussing and crying 19 …”
Section: Discussionsupporting
confidence: 90%
“…For example, Tang [ 10 ] showed that detailed consultation and guidance by professional medical personnel are useful for improving the condition of GDM patients. It can be seen that nursing methods have a key positive effect on GDM patients and infants [ 11 ]. The “high-quality nursing service demonstration project” is an important guiding measure for the reform of nursing work in our country at present [ 12 ] and is also an important measure for establishing a patient-centered nursing service concept in China [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among Asian immigrants, two studies in the UK ( 94 , 95 ) and one study in the US ( 96 ) with sample sizes ranging from 382 to 6 060 reported a consistent association between GDM and childhood obesity across all races and ethnic groups. The magnitude in such association between NHW women and Asian female immigrants was similar.…”
Section: Resultsmentioning
confidence: 97%